Conspicuous Consumption, Inequality and Debt: The Nature of Consumption‐driven Profit‐led Regimes. (25th July 2014) - Kapeller, Jakob; Schütz, Bernhard
Abstract This paper extends the theoretical concept of wage‐led and profit‐led demand regimes by incorporating relative consumption concerns. Specifically, it integrates the Veblenian concept of conspicuous consumption into the Bhaduri–Marglin model by assuming that relative consumption concerns matter primarily within the working class. If in such a framework the profit share increases and the corresponding decrease in workers' income is distributed unevenly, efforts to 'keep up with the Joneses' may increase consumption and, hence, lead to a consumption‐driven profit‐led regime.